1999
DOI: 10.1046/j.1365-2672.1999.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the rumen ciliate protozoa for methane suppression caused by coconut oil

Abstract: K RE UZ E R. 1999. Diets containing either coconut oil or rumen-protected fat (54 g kg −1 dry matter each) were supplied to Rumen Simulation Technique fermenters filled with faunated and defaunated rumen fluid in a 2 × 2 factorial design. Defaunation immediately reduced methane formation by about 40% with each diet. With coconut oil, methane gradually declined in faunated and defaunated rumen fluid. Finally, the extent of methane suppression was similar, both with coconut oil and with defaunation. Independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
95
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 19 publications
(32 reference statements)
23
95
2
7
Order By: Relevance
“…In our concomittant in vitro study using the same plant material and methods (in press), STA showed at t ½ by 60% lower n-butyrate than the control CYN, which has been related to protozoa metabolism (Dohme et al, 1999). It is possible that the protozoa was more affected by STA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In our concomittant in vitro study using the same plant material and methods (in press), STA showed at t ½ by 60% lower n-butyrate than the control CYN, which has been related to protozoa metabolism (Dohme et al, 1999). It is possible that the protozoa was more affected by STA.…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that the protozoa was more affected by STA. Interaction between methanogens and protozoa is well documented in studies with tanniferous plants (Wang et al, 1994;Hess et al, 2003;Abdalla et al, 2012), saponins (Hess et al, 2003), and oil (Dohme et al, 1999;Krause et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…A decrease in protozoa number by Supplementation of unsaturated fatty acid reduced the protozoan population in sheep rumen has also been suggested earlier 54 .It has been found that inclusion of CO in the diet caused reduction in protozoan number 55 . Decrease in methane production is also accompanied by reduction in the number of protozoa resulting from increased oil concentration.…”
Section: Protozoa Numbermentioning
confidence: 59%
“…Likewise, saponin in S. rarak extract did not reduce the archaeal or methanogen RNA concentration either in vitro or in vivo studies (Wina et al, 2005a). Dohme et al (1999) also showed that methane suppression by defaunation is not accompanied by a reduction in methanogen counts. In most studies, methanogens have been measured using the anaerobic culture technique and cell counts of methanogens were measured as colony-forming units, or, methanogens have been measured using in situ hybridisation technique.…”
Section: Plants Containing Saponinsmentioning
confidence: 95%
“…In most studies, methanogens have been measured using the anaerobic culture technique and cell counts of methanogens were measured as colony-forming units, or, methanogens have been measured using in situ hybridisation technique. These studies are limited to the effects of various oils and individual fatty acid supplementation (Dohme et al, 1999 and2001;Hess et al, 2004). The methanogen cell count determination using culture-based techniques has the disadvantages of non-specificity and that not all microorganisms can be cultured (Makkar and McSweeney, 2005).…”
Section: Plants Containing Saponinsmentioning
confidence: 99%